Sistem Informasi Penerimaan Siswa Baru Berbasis Web pada SMK Muhammadiyah 7 Jakarta - Rahman, Lupi; Murdiani, Deni (Jurnal Etnik: Ekonomi-Teknik, 2021)
The problem that often occurs in the implementation of new student admissions is the delay in time from the decision holder who is in charge of distributing new student admission circulars that are not on time while prospective students have come to school and are ready to register, in the admission process they still use the form. in paper form so that prospective students are required to come to school and fill out data, there is no system capable of assisting the admissions process, and files used for registration are sometimes lost when they are needed to check student data. In order to create an adequate system that is able to overcome the problems that occur, it is necessary to create a system that can overcome the process of accepting new students quickly and according to the planned schedule. penelitian This provides a solution by reviewing some of the theory and field observations in order to design new admissions information system based on web. The application development methodology that the author uses is the SDLC (System Develop Life Cycle) method with the waterfall process model until the testing stage. The programming language used is PHP and utilizes the MySQL database as a database server. This New Student Admissions information system provides information in the form of registration activities for new prospective students, verification of registration requirements, and announcement of written test results for all prospective new students who register at SMK Muhammadiyah 7. This New Student Admission application provides convenience in carrying out the Admission process. New Students, especially for prospective new students who are outside Jakarta, or for prospective new students who are quite far from the location of SMK Muhammadiyah 7